Hydrogen Storage - Liu, Jianjun (IntechOpen, 2012)
Hydrogen, as an energy carrier, is widely regarded as a potential cost effective, renewable, and clean energy alternative to petroleum in order to mitigate energy shortage and global climate warming issues that the world is currently facing. However, storage of hydrogen is a substantial challenge, especially for applications in vehicles with fuel cells that use proton-exchange membranes (PEMs). Therefore, scientific community has started focusing their research activities on developing advanced hydrogen storage materials through nanotechnology. The book presents a wide variety of nanostructured materials used for application in hydrogen storage, covering chemical and physical storage approaches. The research topics include computational design, synthesis, processing, fabrication, characterization, properties and applications of nanomaterials in hydrogen storage systems.